Geographic proximity is associated with transmission of suicidal behaviour among siblings. (10th June 2019) - Edwards, A. C.; Ohlsson, H.; Mościcki, E. K.; Sundquist, J.; Sundquist, K.; Kendler, K. S.
Abstract : Objective: The aim of this study was to clarify the role of 'contagion', or social transmission, in risk of suicidal behaviour (SB) among siblings. Methods: We followed Swedish sibling pairs until one of them (S1; N  = 111, 848) was registered for a suicide attempt or completion. We tested the effect of geographic proximity between siblings on risk of a first SB registration of S1's sibling (S2). To control for familial confounding, we conducted complementary analyses of sibling trios ( N  = 701), comparing risk in different siblings as a function of their respective proximity to S1. Results: The best‐fitting model across sibling pairs included an effect of distance between siblings (HR = 0.96, 95% CI = 0.93–0.99). Hazard ratios declined quickly up to 25 km and largely stabilized beyond 150 km. Across all pairs, a larger age difference between siblings was associated with reduced SB risk (HR = 0.96 95% CI = 0.93–0.98). Findings were consistent within the sibling trios. Conclusions: Consistent with the concept of suicide contagion, risk of suicidal behaviour subsequent to a sibling's suicide completion or attempt is higher as a function of sibling closeness. These findings are robust to potentially confounding familial factors.